Analisis Saluran Pemasaran Tomat (Solanum lycopersicum L.) pada Kelompok Tani Cijapati di Desa Mekarlaksana - Yanti, Widi; Pardani, Cecep (Ma'soem University, 2024)
Marketing channels that run well will reap huge profits. This research aims to find out; 1) marketing channels for tomatoes in the Cijapati farmer group in Mekarlaksana Village, Cikancung District, Bandung Regency, 2) the amount of margin, costs and profits from marketing tomatoes in the Cijapati farmer group in Mekarlaksana Village, Cikancung District, Bandung Regency, 3) share of the price received by farmers (farmer's share) in the Cijapati farmer group in Mekarlaksana Village, Cikancung District, Bandung Regency. This research is descriptive quantitative using the case study method. The sample of respondents was taken as many as 23 people using the census and snowball sampling method. The research results show that The Cijapati farmer group has established a linear marketing channel for their tomatoes. The distribution process starts from farmers as producers, then moves to wholesalers as main distributors. After that, the tomatoes will be distributed to retailers before finally being sold to final consumers. 2) Total marketing margin of IDR 2,500. Total marketing costs reached IDR 412 from the total expenditure during marketing. From the difference between marketing margin and marketing costs, a marketing profit of IDR 2,088 is obtained. 3) Farmers receive 50% of the total marketing margin of IDR 2,500, which is IDR 1,250, while the remainder is used for marketing costs and profits.